Odpowiedzi

2010-04-05T19:26:28+02:00
[2x2√2 x4 ^4/3 x1/8 ⁻² ]/[1/2x 16 ^- 3/4]=
[2x2*2^1/2 x2² ^4/3 x8 ² ]/[2⁻¹x2⁴ ^- 3/4]=
[2²*2^1/2 x2 ^8/3 x(2³) ² ]/[2⁻¹x2 ^- 3]=
[2^2 i 1/2 x2 ^8/3 x 2⁶ ]/[2⁻⁴]=
[2^(2 i 1/2 +8/3 +6) ]/[2⁻⁴]=
[2^(8 i 3/6 +16/6 ) ]/[2⁻⁴]=[2^(8 i 19/6 ) ]/[2⁻⁴]=2^(8 i 19/6+4)=2^12 i 19/6
=2^91/6
2010-04-05T19:36:36+02:00
[2x2√2 x4 ^4/3 x1/8 ⁻² ]/[1/2x 16 ^- 3/4]=[2x2*2^1/2 x2² ^4/3 x8 ² ]/[2⁻¹x2⁴ ^- 3/4]=[2²*2^1/2 x2 ^8/3 x(2³) ² ]/[2⁻¹x2 ^- 3]=[2^2 i 1/2x2 ^8/3 x 2⁶ ]/[2⁻⁴]=[2^(2 i 1/2 +8/3 +6) ]/[2⁻⁴]=[2^(8 i 3/6 +16/6 ) ]/[2⁻⁴]=[2^(8 i 19/6 ) ]/[2⁻⁴]=2^(8 i 19/6+4)=2^12 i 19/6=2^91/6